PENERAPAN METODE DISKUSI KELAS PADA MATERI HAK DAN KEWAJIBAN UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS III - Sasabillah; Aprian P; Cici S; Ajeng R; Anita D; Destrinelli; Desy R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Speaking is a fundamental skill that needs to be developed early at the elementary level. This skill not only supports daily communication but also serves as an essential foundation for active and participatory learning. However, many students still struggle to express ideas, participate in discussions, and communicate orally in the classroom. These challenges highlight the need for more interactive teaching strategies. This study aims to explore the implementation of classroom discussion methods in Civic Education (PKn) lessons on the topic of rights and obligations as an effort to improve students’ speaking skills. The research employed a qualitative approach using a Classroom Action Research (CAR) design, conducted in two cycles involving 23 third-grade students at SDN 56/I Desa Aro. Data were collected through observation, interviews, documentation, and field notes, and analyzed using descriptive qualitative techniques to understand the learning process and its impact on students’ speaking development.